ANALISIS PERHITUNGAN DAN PELAPORAN PAJAK HOTEL DAN RESTORAN PADA HOTEL WHIZ PRIME MANADO - Senduk, Monica; Saerang, David P. E.; Morasa, Jenny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
As the development of tourism industry in Manado City, make a potential impact for the hotel industry in Manado City. Thus we must pay more attention to the tax treatment in the hospitality business, both in its application and calculation. The purpose of this study was to find out the application of hotel tax accounting at Whiz Prime Hotel Manado. This type of research is descriptive. Data obtained through field observations, interviews and library research. Data were then analyzed using qualitative descriptive analysis methods. The results showed that the calculation and deduction of local taxes on Whiz Prime Hotel Manado already refers to existing tax regulations. Hotel tax calculation in every transaction is done at the end of every month by Whiz Prime Hotel. Although the application and calculation have been implemented according to the existing regulations, but there are still those who do not understand what supporting services are in hotel taxes. For this reason, Whiz Prime Hotel is expected to maintain existing performance and improve understanding and application, so that services and human resources can be better.